Toward an Afric-ecological education: an alternative strategy for the development of Sub-Saharan African countries - Keita, Fatoumata (Ciência & Trópico, 2013)
ABSTRACTThe purpose of this article is to discuss the paramount necessityto implement an adequate educational system in order to achievesustainable development in the SSA countries with a focus inMali, one of the poorest countries in the world with an endemiceducational crisis. It is a truism that education is the cornerstone ofdevelopment. In this respect, any strategy of development in SSAshall start with a change in the pedagogy. This reform implies notonly a rethinking of knowledge production and teaching in Africaas to take into account the current needs of the masses, their culturaland historical experiences as well as their environmental problems;but it also involves a curriculum development which makesuniversities and schools spearheads of larger social transformationsand communal uplift in order to attain the Millenium DevelopmentGoals as well as mainstream a genuine sustainable development. Inthis connection, this paper makes a case for the implementation ofan Afric-ecological curriculum in order to deal effectively with themultidimensional challenges of development and education in theSSA, particularly in Mali. Such a curriculum has the advantage tocombine an afrocentric perspective to teaching and learning with astrong ecological awareness. In addition, it is geared toward reducinginequalities between men and women, and between rural and urbanwomen in terms of educational and job opportunities.KEYWORDS: Development. Education. Curriculum. Afrocentricity/Africology.Educação Africo-ecológica uma estra-tégia alternativa para o desenvolvi-mento de países da África SubsaarianaRESUMOO objetivo deste artigo é discutir a necessidade primordial deimplementar um sistema educacional adequado, a fim de alcançaro desenvolvimento sustentável nos países da África Subsaariana(ASS), com foco em Mali, um dos países mais pobres do mundo,com uma crise endêmica educacional. É um truísmo dizer que aeducação é a base do desenvolvimento. A este respeito, qualquerestratégia de desenvolvimento da ASS terá início com uma alteraçãona pedagogia. Essa reforma implica não apenas uma reflexão sobre aprodução do conhecimento e do ensino na África como também temem conta as necessidades atuais das massas, de suas experiênciasculturais e históricas, bem como seus problemas ambientais, alémdo envolvimento de um desenvolvimento curricular que faz com queas universidades e escolas lancem grandes transformações sociaispara atingir os objetivos de desenvolvimento do milênio, bemcomo integrar um verdadeiro desenvolvimento sustentável. Nessecontexto, o presente trabalho faz um caso para a implementaçãode um currículo Africo-ecológico, a fim de lidar eficazmente comos desafios multidimensionais de desenvolvimento e de educaçãoparticularmente em Mali. Um currículo tem a vantagem de combinaruma perspectiva afrocêntrica de ensino e aprendizagem com umaforte consciência ecológica. Além disso, ele é voltado para a reduçãodas desigualdades entre homens e mulheres e entre mulheres rurais eurbanas em termos de oportunidades de educação e trabalho.PALAVRAS-CHAVE: Desenvolvimento. Educação. Currículo.Afrocentricidade/Africologia.